Temperature Variations of Forced Convection in Porous Media for Heating and Cooling Processes: Internal Heating Effect of Viscous Dissipation - Hung, Y.-M.; Tso, C. P. (2008)
An analytical study on fully developed forced convection in a homogeneous porous medium is reported. Incorporating the internal heating effect of viscous dissipation, closed form solutions of the temperature distributions in the transverse direction are obtained and analyzed for both heating and cooling processes. Variations of Nusselt number as a function of Darcy number and Brinkman number and the existence of singularity in Nusselt number are also discussed